2020
DOI: 10.1080/13102818.2020.1736951
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine can alleviate inflammation and delay the growth of lung cancer during low-dose radiotherapy of non-small cell lung cancer

Abstract: This study investigated the expression of inflammatory factors in tumour tissues, monocytes and blood of non-small cell lung cancer (NSCLC) patients taking tetrandrine (Tet) during low-dose radiotherapy. Sixty NSCLC patients underwent surgical resection of lung cancer after low-dose radiotherapy. Thirty patients did not take Tet (control group) and the other thirty patients took Tet during radiotherapy (experimental group). Lung cancer tissues were collected from patients, and tumour-adjacent tissues were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Inflammation is a physiological response of the body to stimuli such as injury or infection, which can cause tissue damage and disease development. 42 Detecting inflammatory tissue can provide information about the type, severity, and progression of the disease. This helps in early diagnosis and treatment of the disease, improving the treatment outcomes and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation is a physiological response of the body to stimuli such as injury or infection, which can cause tissue damage and disease development. 42 Detecting inflammatory tissue can provide information about the type, severity, and progression of the disease. This helps in early diagnosis and treatment of the disease, improving the treatment outcomes and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…The application of AIFCM in this regard is merely in its initial stage, and exciting progress can be expected in the near future. Radiosensitization effect, inducing apoptosis via miR-34a/Sirt1/p53 signaling pathway; attenuating angiogenesis [189,193] Radiotherapy Coptis chinensis Berberine Inhibiting the expression of HIF-1 and VEGF, reversing radioresistance [190] Radiotherapy Magnolia Honokiol Suppressing the Notch signaling pathway, inhibiting radiation resistance and CSCs promotion [191] Radiotherapy Rhizoma zeodaria β-elemene Radiosensitization effect, suppressing the Prx-1/NF-kB /iNOS pathway, inhibiting EMT and CSC [192] Radiotherapy Radix stephania tetrandrae Tetrandrine Reducing the inflammatory factors, alleviating inflammation [194] Immunotherapy Rhizoma polygoni cuspidati Pigenin Down-regulation of p-EGFR, p-Akt, p-STAT3 and Cyclin D1, promotion of antibody-mediated cytotoxicity and apoptosis [207] Immunotherapy Garcinia hanburyi Gambogic acid Promoting antibody-mediated cytotoxicity [208] Immunotherapy Rhizoma polygoni cuspidati…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wu's group reported that EGCG could attenuate the induction of angiogenesis by gamma radiation in breast cancer patients within the combination of EGCG and ionizing radiation 193 . Moreover, Liang et al used tetrandrine to reduce the inflammatory factor release of A549 tumor tissue to alleviate inflammation and improve the tumor inhibition effect in radiotherapy 194 .…”
Section: Combination Modalitiesmentioning
confidence: 99%
“…2 Inflammation can clear the original damage and necrotic cells and tissues damaged during the inflammatory process, initiating tissue repair. 3 Previous studies show that immune cells, blood vessels, and molecular mediators are closely related to the formation of inflammation, while reactive oxides and viscosity are closely related to cellular inflammation and the pathogenesis of certain diseases. 4 In organisms, H 2 O 2 and Cl − are taken by peroxidase catalyzed reactions to form hypochlorite ions (ClO − ).…”
Section: Introductionmentioning
confidence: 99%